Lipid Metabolism Regulates Oxidative Stress and Ferroptosis in RAS-Driven Cancers: A Perspective on Cancer Progression and Therapy - Bartolacci, Caterina; Andreani, Cristina; El-Gammal, Yasmin; Scaglioni, Pier Paolo (Frontiers in Molecular Biosciences, 2021)
HRAS, NRAS and KRAS, collectively referred to as oncogenic RAS, are the most frequently mutated driver proto-oncogenes in cancer. Oncogenic RAS aberrantly rewires metabolic pathways promoting the generation of intracellular reactive oxygen species (ROS). In particular, lipids have gained increasing attention serving critical biological roles as building blocks for cellular membranes, moieties for post-translational protein modifications, signaling molecules and substrates for ß-oxidation. However, thus far, the understanding of lipid metabolism in cancer has been hampered by the lack of sensitive analytical platforms able to identify and quantify such complex molecules and to assess their metabolic flux in vitro and, even more so, in primary tumors. Similarly, the role of ROS in RAS-driven cancer cells has remained elusive. On the one hand, ROS are beneficial to the development and progression of precancerous lesions, by upregulating survival and growth factor signaling, on the other, they promote accumulation of oxidative by-products that decrease the threshold of cancer cells to undergo ferroptosis. Here, we overview the recent advances in the study of the relation between RAS and lipid metabolism, in the context of different cancer types. In particular, we will focus our attention on how lipids and oxidative stress can either promote or sensitize to ferroptosis RAS driven cancers. Finally, we will explore whether this fine balance could be modulated for therapeutic gain.